2023
DOI: 10.1111/1471-3802.12594
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval‐based learning in special education

Abstract: Retrieval-based learning has been investigated in various populations. The present study examined retrieval-based learning in a sample of students at a special-needs school with educational tracks for learning and mental development. In addition, a comparison group of students at a regular school was examined. Learning conditions were manipulated within participants. In a first session, participants either received restudy cycles only, or they received alternating test and restudy cycles. A second session then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Recently, Knouse et al (2020) and Minear et al (2023) found that students with ADHD and TD students benefitted similarly from retrieval practice relative to repeated study when learning key term definitions and Swahili-English word pairs, respectively. These findings are consistent with recent evidence that the size of the benefit of retrieval practice over restudying is unrelated to cognitive ability ( Jonsson et al, 2021 ) and that special education students benefit from retrieval practice ( Tempel and Sollich, 2023 ).…”
Section: Introductionsupporting
confidence: 91%
“…Recently, Knouse et al (2020) and Minear et al (2023) found that students with ADHD and TD students benefitted similarly from retrieval practice relative to repeated study when learning key term definitions and Swahili-English word pairs, respectively. These findings are consistent with recent evidence that the size of the benefit of retrieval practice over restudying is unrelated to cognitive ability ( Jonsson et al, 2021 ) and that special education students benefit from retrieval practice ( Tempel and Sollich, 2023 ).…”
Section: Introductionsupporting
confidence: 91%